A flame retardant rigid polyurethane foam system including functionalized graphene oxide. (11th August 2018) - Gao, Ming; Li, Junfei; Zhou, Xuan
Abstract : A functionalized graphene oxide (fGO) was prepared by graphene oxide (GO), boric acid and 3‐aminopropyltriethoxysilane in an ethanol aqueous solution using ultrasonic agitation. Its structure was characterized by the Fourier transform infrared (FTIR), X‐ray diffraction (XRD), thermogravimetric analysis (TG), and elemental analysis. Subsequently, the fGO was incorporated into the flame‐retardant‐polyurethane (FRPU) system, in which fGO as a synergist and reinforcing agent, expandable graphite (EG), and dimethyl methylphosphonate (DMMP) as flame retardants, to improve its the flame‐retardancy and mechanical properties, evidenced by the limiting oxygen index (LOI), vertical burning test (UL‐94) test and the cone calorimeter test (CONE). The LOI value of FRPU/fGO composites reached 28.1% by addition of 0.25 phr fGO and 10 phr EG/DMMP, and its UL‐94 test reached V‐0 rating. The CONE results revealed that fGO could significantly enhance flame retardant properties of FRPU composites, and the peak heat release rate (PHRR) values value of FRPU/fGO remarkably reduced by 32.9%. Moreover, fGO indeed enhanced the mechanical properties of rigid polyurethane foam (RPUF). POLYM. COMPOS., 40:E1274–E1282, 2019. © 2018 Society of Plastics Engineers